Creative, efficient and effective project management - Kliem, Ralph L. (CRC Press, 2014)
Creativity and project management -- Creative thinking abilities -- Groups and creativity -- Challenges and constraints -- Laying the groundwork for a creative environment -- Common creativity tools and techniques -- Creativity life cycle models -- Creativity and the defining process -- Creativity and the organizing process -- Creativity and the planning process -- Creativity and the executing process -- Creativity and the monitoring and controlling process -- Creativity and the closing process -- Baker's dozen of takeaways.